Difference between revisions of "009C Sample Midterm 2, Problem 5"

From Math Wiki
Jump to navigation Jump to search
Line 36: Line 36:
 
|Let &nbsp;<math style="vertical-align: -5px">a\in (-2R,2R).</math>&nbsp; Then, &nbsp;<math style="vertical-align: -13px">\frac{a}{2} \in (-R,R).</math>&nbsp;
 
|Let &nbsp;<math style="vertical-align: -5px">a\in (-2R,2R).</math>&nbsp; Then, &nbsp;<math style="vertical-align: -13px">\frac{a}{2} \in (-R,R).</math>&nbsp;
 
|-
 
|-
|So,  
+
|Since &nbsp;<math style="vertical-align: -19px">\sum_{n=0}^\infty c_nx^n</math>&nbsp; converges in the interval &nbsp;<math style="vertical-align: -5px">(-R,R),</math>&nbsp;
 
|-
 
|-
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\sum_{n=0}^\infty c_n\bigg(\frac{a}{2}\bigg)^n</math>
+
|&nbsp; <math>\sum_{n=0}^\infty c_n\bigg(\frac{a}{2}\bigg)^n</math>&nbsp; converges.
 
|-
 
|-
|converges by assumption.
+
|Since &nbsp;<math style="vertical-align: 0px">a</math>&nbsp; was an arbitrary number in the interval &nbsp;<math style="vertical-align: -5px">(-2R,2R),</math>&nbsp;
|-
 
|Since &nbsp;<math style="vertical-align: 0px">a</math>&nbsp; was an arbitrary number in the interval &nbsp;<math style="vertical-align: -5px">a\in (-2R,2R),</math>&nbsp;
 
 
|-
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\sum_{n=0}^\infty c_n\bigg(\frac{x}{2}\bigg)^n</math>
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\sum_{n=0}^\infty c_n\bigg(\frac{x}{2}\bigg)^n</math>
Line 53: Line 51:
 
!Step 1: &nbsp;
 
!Step 1: &nbsp;
 
|-
 
|-
|
+
|Assume that the power series &nbsp;<math style="vertical-align: -19px">\sum_{n=0}^\infty c_nx^n</math>&nbsp; converges.
 +
|-
 +
|Let &nbsp;<math style="vertical-align: 0px">R</math>&nbsp; be the radius of convergence of this power series.
 +
|-
 +
|So, the power series
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -19px">\sum_{n=0}^\infty c_nx^n</math>&nbsp;
 +
|-
 +
|converges in the interval &nbsp;<math style="vertical-align: -5px">(-R,R).</math>&nbsp;
 
|}
 
|}
  
Line 59: Line 65:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|
+
|Let &nbsp;<math style="vertical-align: -5px">a\in (-R,R).</math>&nbsp; Then, &nbsp;<math style="vertical-align: -5px">-a \in (-R,R).</math>&nbsp;
 +
|-
 +
|Since &nbsp;<math style="vertical-align: -19px">\sum_{n=0}^\infty c_nx^n</math>&nbsp; converges in the interval &nbsp;<math style="vertical-align: -5px">(-R,R),</math>&nbsp;
 +
|-
 +
|&nbsp;<math>\sum_{n=0}^\infty c_n(-a)^n</math>&nbsp; converges.
 +
|-
 +
|Since &nbsp;<math style="vertical-align: 0px">a</math>&nbsp; was an arbitrary number in the interval &nbsp;<math style="vertical-align: -5px">(-R,R),</math>&nbsp;
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\sum_{n=0}^\infty c_n(-x)^n</math>
 +
|-
 +
|converges in the interval &nbsp;<math style="vertical-align: -5px">(-R,R).</math>&nbsp;
 
|}
 
|}
  

Revision as of 16:27, 23 April 2017

If    converges, does it follow that the following series converges?

(a)  

(b)  


Foundations:  
If a power series converges, then it has a nonempty interval of convergence.


Solution:

(a)

Step 1:  
Assume that the power series    converges.
Let    be the radius of convergence of this power series.
So, the power series
        
converges in the interval   
Step 2:  
Let    Then,   
Since    converges in the interval   
    converges.
Since    was an arbitrary number in the interval   
       
converges in the interval   

(b)

Step 1:  
Assume that the power series    converges.
Let    be the radius of convergence of this power series.
So, the power series
        
converges in the interval   
Step 2:  
Let    Then,   
Since    converges in the interval   
   converges.
Since    was an arbitrary number in the interval   
       
converges in the interval   


Final Answer:  
    (a)     converges
    (b)     converges

Return to Sample Exam